Prediction of the risk of developing diabetes mellitus among Bangladeshi adults by using risk assessment score - Akter, Nazma (BIRDEM Medical Journal, 2019)
Background: Diabetes mellitus (DM) is considered as one of the major health problems worldwide. The rising prevalence of type 2 diabetes mellitus (T2DM) in Bangladesh is primarily attributed to rapid urbanization and associated changes in lifestyle, such as sedentary lifestyle, higher calorie food intake and stressful life. Studies support the utilization of riskassessment scoring systems in quantifying individual’s risk for developing T2DM. Thus, a simple risk-assessment scoring system for early screening of T2DM among Bangladeshi adults will be beneficial to identify the high-risk adults and thus taking adequate preventive measures in combating DM.The purpose of the study was to calculate the risk assessment score of developing T2DM within 10 years among Bangladeshi adults. Methods: The cross-sectional observational study was carried out in the outpatient department (OPD) of Medicine, MARKS Medical College & Hospital, a tertiary care hospital in Dhaka, Bangladesh from February 2018 to July 2018 among randomly sampled 205 adult subjects. Subjects undiagnosed with diabetes mellitus and had previous history of high blood glucose during pregnancy or other health examination (i.e. impaired fasting glucose, impaired glucose tolerance or gestational diabetes mellitus) were included. From a review of literature regarding risk factors of developing DM in Bangladesh, the Finnish Diabetes Risk Score (FINDRISC) system was found to be more useful for the Bangladeshi adults. The Finnish Diabetes Risk Score (FINDRISC) questionnaire was used to collect the data including demographic characteristics and different risk factors and to calculate total risk score for predicting the risk of developing T2DM within 10 years. Results: Among 205 subjects, male and female were 57.1% and 42.9% respectively. The Mean (±SD) age of the study subjects was 37.64±1.07 years. In this study, both non-modifiable and modifiable risk factors showed statistically significant association with the FINDRISC among Bangladeshi adults (p<0.05). There was a significant association among FINDRISC with history of previous high blood glucose, and treated hypertensive Bangladeshi adults.33.65% of the Bangladeshi adults had slightly elevated diabetes risk score (DRS). This study predicts that 17.55% of the Bangladeshi adults may have moderate to high risk to develop T2DM within the consecutive 10 years. Conclusion: This study provides a simple, feasible, non-invasive and convenient screening FINDRISC tool that identifies individuals at risk of having T2DM. People with high risk of DM should be referred for early intervention and changes to a healthy lifestyle and primary prevention to prevent or delay the onset of T2DM. Birdem Med J 2020; 10(1): 40-47